Active assessment in English : - Keogh, Brenda (Routledge, 2008)
This book shows you how to do it. The thinking behind the highly influential 'Assessment for Learning' approach is translated into usable and practical strategies for all those teaching literacy in primary and secondary classrooms. The authors show how thinking, learning and assessment can be linked together in a creative and integrated fashion, so that thinking promotes learning, learning enables assessment to take place and assessment acts as a stimulus to both thinking and learning